2017
DOI: 10.4236/ojped.2017.74028
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Fatal Outcomes during Severe Malaria in Children at the HKM University Teaching Hospital of Cotonou-Benin

Abstract: Introduction: Malaria particularly affects children in sub-Saharan African countries. This study aimed to investigate the factors associated with death in cases of severe childhood malaria to better understand the determinants of death in these children. Patients and Methods: This cohort, descriptive and analytical study was conducted from April 1 to August 15, 2015, at the CNHU-HKM pediatric clinic in Cotonou. Recruitment was exhaustive for all patients under 15 years of age who were admitted for severe malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Another study in Ghana reported a mortality of 11.2% [ 17 ]. Other studies found with high incidences of death include a study on determinants of fatal outcomes of severe malaria in children in Cotonou-Benin that reported a mortality of 13.1% mortality [ 26 ]. Furthermore, a study on SM and risk factors for mortality in the Democratic Republic of Congo that reported even higher rates of 28.3% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Ghana reported a mortality of 11.2% [ 17 ]. Other studies found with high incidences of death include a study on determinants of fatal outcomes of severe malaria in children in Cotonou-Benin that reported a mortality of 13.1% mortality [ 26 ]. Furthermore, a study on SM and risk factors for mortality in the Democratic Republic of Congo that reported even higher rates of 28.3% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reports haemoglobinuria as risk factors for death, but is not frequently reported in other series outside of studies in Eastern Uganda [ 14 , 28 ]. The commonly reported predictors of mortality in SM include coma and convulsions [ 20 , 26 , 27 ], malnutrition [ 17 , 27 ], cerebral malaria [ 21 , 22 ], and hypoglycaemia [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that in severe malaria, neurological manifestations appear within the first 12 h of admission [63] and is fatal without treatment [64]. Severe malaria treatment implies, in addition, supportive care to control complications of especially poor prognosis factors such as severe anemia, respiratory distress, bacterial co-infections and acute renal failure [65][66][67][68][69][70]. Blood, oxygen, dialysis and mechanical ventilation [71] may be necessary for an appropriate treatment of severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Secara signifikan faktor prediktor kematian yang kuat ialah koma dan kejang berulang. 9,18 Malaria serebral didefinisikan dengan Blantyre coma scale (BCS) ≤2 dengan berapapun densitas parasitnya. Koma (BCS<3) berhubungan dengan peningkatan risiko kematian.…”
Section: Bahasanunclassified
“…12 Hipoglikemik secara bermakna dan independen berhubungan dengan luaran atau hasil yang buruk termasuk kematian. 14,18 Prostrasi memiliki hubungan bermakna dengan kematian. 14 Prostrasi didefinisikan dengan kelemahan generalisata yang ditandai dengan ketidakmampuan seseorang untuk duduk maupun minum tanpa bantuan.…”
Section: Bahasanunclassified